The Criminal Act of Obscenity toward Childrenn In terms of the Law on Child Protection - Wandrinus Hulu; Fitasiani Laia; Taufika Hidayati (LEGAL BRIEF, 2023)
Child abuse is a sexual crime committed by a man/woman against minors, both men and women, with violence or without violence. The aim of the research is to find out the protection for victims of criminal acts of obscenity and what sanctions are given to the perpetrators in terms of the law. The type of research in this paper is normative with a statutory and contextual approach. While the specification of this research is descriptive analysis. The data used is secondary data consisting of primary legal materials in the form of Law No. 35 of 2014 amendment to Law No. 23 of 2002 concerning Child Protection, the Criminal Code, Law No. 31 of 2014, Law No. 39 of 1999, and secondary legal materials such as books -books, journals, and writings related to the research title. The criminal act of molestation of children is very contrary to religious and moral norms. For this reason, protection for children as victims of criminal acts of obscenity will receive compensation and compensation for losses that have been experienced by victims, provide medical services, and receive legal protection, especially when they become witnesses to what they have experienced. So the author's suggestion in this case is that the application of sanctions for perpetrators according to this law is actually applied by judges in making decisions so that it becomes a deterrent effect for perpetrators. And law enforcers must pay attention to what is the right of children as disturbing victims in accordance with what is mandated by law.